Inhibition by ATP of Hippocampal Synaptic Transmission Requires Localized Extracellular Catabolism by Ecto-Nucleotidases into Adenosine and Channeling to Adenosine A(1) Receptors - Cunha, Rodrigo A. (J Neurosci, 1998)
ATP analogs substituted in the γ-phosphorus (ATPγS, β,γ-imido-ATP, and β,γ-methylene-ATP) were used to probe the involvement of P(2) receptors in the modulation of synaptic transmission in the hippocampus, because their extracellular catabolism was virtually not detected in CA1 slices. ATP and γ-substituted analogs were equipotent to inhibit synaptic transmission in CA1 pyramid synapses (IC(50) of 17–22 μm). The inhibitory effect of ATP and γ-phosphorus-substituted ATP analogs (30 μm) was not modified by the P(2) receptor antagonist suramin (100 μm), was inhibited by 42–49% by the ecto-5′-nucleotidase inhibitor and α,β-methylene ADP (100 μm), was inhibited by 74–85% by 2 U/ml adenosine deaminase (which converts adenosine into its inactive metabolite-inosine), and was nearly prevented by the adenosine A(1) receptor antagonist 1,3-dipropyl-8-cyclopentylxanthine (10 nm). Stronger support for the involvement of extracellular adenosine formation as a main requirement for the inhibitory effect of ATP and γ-substituted ATP analogs was the observation that an inhibitor of adenosine uptake, dipyridamole (20 μm), potentiated by 92–124% the inhibitory effect of ATP and γ-substituted ATP analogs (10 μm), a potentiation similar to that obtained for 10 μm adenosine (113%). Thus, the present results indicate that inhibition by extracellular ATP of hippocampal synaptic transmission requires localized extracellular catabolism by ecto-nucleotidases and channeling of the generated adenosine to adenosine A(1) receptors.